International patent systems strength 1998-2011 - Papageorgiadis, Nikolaos; Cross, Adam R.; Alexiou, Constantinos (Elsevier, 2014)
In this paper we report on a composite index of international patent systems strength for 48 developing and industrialized countries annually from 1998 to 2011. Building upon earlier indices we develop a conceptual framework informed by transaction cost theory and derive measures which emphasize the importance of enforcement-related aspects of the patent system of countries. Findings reveal harmonization of the regulative aspects of patent protection internationally in the post-TRIPs era but not of overall national patent systems. The index should inform studies on the relationship between national patent systems and a range of international business and other phenomena.
Keywords: Intellectual property; Patent; National patent systems index; Patent enforcement; Patent system development